RELATIONSHIPS BETWEEN PRINCIPAL ROCK TYPES OF THE ANORTHOSITE-GRANITE ASSOCIATION OF THE UKRAINIAN SHIELD, AS INFERRED FROM THE DISTRIBUTION OF RARE-EARTH ELEMENTS - Sukhanov M.K.; Tarasenko V.S.; Lyapunov S.M.; Yermolayev B.V. (My University, 1988)
The anorthosite-granite association is widespread in eastern Europe, where its typical representatives are the well-known composite intrusive complexes of the Ukrainian shield, consisting of two rock groups - the mafic, with anorthosite, gabbro, gabbronorite and troctolite, and the granitic, with rapakivi granite, syenite and monzonite. There are different views concerning the genetic relationships between these rocks groups; some authors regard them as independent, but others assume that they are differentiation products of the same parent magma. This paper discusses geochemical data on rare-earth elements characteristic of the anorthosite-granite association of the Ukrainian shield in the Korosten' batholith and, from them, draws some conclusions concerning the relationships here between its constituent rocks. Study materials, methods and results are discussed.